2018
DOI: 10.14236/jhi.v25i3.1012
|View full text |Cite
|
Sign up to set email alerts
|

Community-based screening for cardiovascular risk using a novel mHealth tool in rural Kenya

Abstract: BackgroundAn increasing burden of cardiovascular disease (CVD) in low-resource settings demands innovative public health approaches.ObjectivesTo design and test a novel mobile health (mHealth) tool for use by community health workers (CHWs) to identify individuals at high CVD risk who would benefit from education and/or pharmacologic interventions.MethodsWe designed and implemented a novel two-way mobile phone application, ‘AFYACHAT’, to rapidly screen for the CVD risk in rural Kenya. AFYACHAT collects and sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 18 publications
1
33
0
2
Order By: Relevance
“…One of the key challenges includes sporadic power supply and lack of power outlets ( 7 , 9 – 11 , 14 16 , 18 , 29 , 30 ). This impacted the ability to power devices, use applications on mobile phones, central database systems interruption, and server downtime during power interruptions ( 20 , 23 , 31 , 32 ). Another notable impact was variation in data reporting, delayed responses, and duplicative work ( 24 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the key challenges includes sporadic power supply and lack of power outlets ( 7 , 9 – 11 , 14 16 , 18 , 29 , 30 ). This impacted the ability to power devices, use applications on mobile phones, central database systems interruption, and server downtime during power interruptions ( 20 , 23 , 31 , 32 ). Another notable impact was variation in data reporting, delayed responses, and duplicative work ( 24 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in Zambia, Tanzania, Uganda, Nigeria and Ethiopia reported use of solar lamps/chargers and power banks to recharge the smart phones ( 2 , 3 , 7 , 8 , 23 , 26 ). In some other settings like Kenya, community health workers used paper to record values, and later sent them when power was restored ( 24 , 31 ). In some studies, it was reported that there were insurgent attacks and cases of phone theft.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a month when Public Health England has launched its online tool to predict your heart age,12 we publish an article by Mannik et al .,13 about how community health workers in rural Kenya have used a mobile app to screen for cardiovascular disease and risk.…”
Section: Mobile Health To Screen For Cardiovascular Diseasementioning
confidence: 99%